PW 1329 Cultural and social practices: implications for policy and practice in road safety. (November 2018) - Kayani, Ahsan; King, Mark; Fleiter, Judy
Abstract : Background: Road safety interventions are typically designed in Western countries, but should be appropriate to the people and communities that implement them and are targeted by them. While institutional and funding issues are frequently considered, little attention has been given to the implications of the prevailing cultures and practices within non-Western societies. Objective: To explore the nature and implications for road safety in non-Western countries of cultural and social practices, using Pakistan as an example. Methods: Individual in-depth interviews were conducted with 30 participants: policy makers, police officers, religious orators, professional drivers (truck, bus and taxi) and general drivers. A combination of purposive, criterion and snowball sampling was used. Findings: There was a relationship between social (importantly religious) and cultural factors, police enforcement and (lack of) awareness of road rules. Fatalism and superstitious practices characterized both intervention targets (drivers) and implementers (police and policy makers). There was a lack of knowledge and awareness of the scientific evidence on crash causation and crash risk among all participants, regardless of education. Conclusion: Cultural and social factors (including religion) have a profound influence on road user behavior, policies and enforcement practices in Pakistan, among both implementers and targets of interventions. Policy implications: Road safety interventions need to take into account cultural and social factors among those who make, use and enforce the 'system' (e.g. policy makers, senior police officers and the highly educated) and among road users in general. Successful governance of road safety in non-Western countries requires promotion of a scientifically-based approach to road user behaviour, and improved professional education for the implementers of interventions as well as the public.